Effective coaching - Cook, Marshall, 1944-; Poole, Laura; McGraw-Hill eBooks (New York, N.Y. : McGraw-Hill Education LLC., 2011)
More than 700,000 Briefcase Books sold! Proven techniques for going from a boss to a coach to maximize the efficiency of every employee.
A. Preface -- Special Features -- Acknowledgments -- B. About the Authors -- 1. The Goals of Good Coaching -- Why Should a Manager Be a Coach? -- Are You Tapping Your Most Valuable Resource? -- Accessibility -- The Benefits of Good Coaching -- Meanwhile, Back at the Publishing Group -- The Coach's Checklist for Chapter 1 -- 2. The Attributes of a Good Coach -- Coaching: Definitions and Distinctions -- Characteristics of a Good Coach -- Translating Attitudes into Actions -- The Coach's Checklist for Chapter 2 -- 3. What Do Your Players Want? -- Looking Beyond the Paycheck -- Three Drives That Motivate Your Staff -- Strategies for Motivational Coaching -- The Coach's Checklist for Chapter 3 -- 4. The Signs of Good Coaching -- Body Language -- "Speaking" Body Language -- The Elements of a Good Coaching Session -- The Coach's Checklist for Chapter 4 -- 5. Asking Good Questions -- Why Ask Questions? -- The Qualities of Effective Coaching Questions -- Seven Major Types of Questions -- Three Techniques for Asking Questions -- The Coach's Checklist for Chapter 5 -- 6. Powerful Listening -- Three Levels of Listening -- Seven Keys to Effective Listening -- Moving Beyond Listening -- The Coach's Checklist for Chapter 6 -- 7. Creating Solutions Through Coaching -- Six Steps to Effective Problem Solving -- Solution-Focused Coaching -- Degrees of Difficulty -- The Coach's Checklist for Chapter 7 -- 8. The Coach as Trainer -- Guidelines for the Coach as Trainer -- Before, During, and After Training -- What Kind of Trainer Are You? -- Four Stages of Learning -- The Learner's Point of View -- An Ideal Training Session -- How Will You Know If It Worked? -- The Coach's Checklist for Chapter 8 -- 9. The Coach as Mentor -- Types of Mentoring -- Effective Mentoring -- Mentoring to Define the Work -- Mentoring to Motivate -- Respecting the Boundaries of Mentoring -- The Coach's Checklist for Chapter 9 -- 10. The Coach as Corrector -- Make It an Encounter, Not a Confrontation -- Positive Specific Action -- Define Consequences Clearly -- Build on the Possible -- Look to the Future -- Performance Killers -- The Coach's Checklist for Chapter 10 -- 11. Coaching Trouble Spots -- Lack of Authentic Purpose -- Anxiety (Yours) -- Fear/Distrust (Theirs) -- Resistance to Change -- Lack of Coaching Skills -- Language Barriers -- Coaching Obstacles -- The Coach's Checklist for Chapter 11 -- 12. Steps to Effective Coaching -- Step 1: Build Rapport -- Step 2: Identify the Issue or Goal -- Step 3: Create Vision -- Step 4: Brainstorm Approaches -- Step 5: Establish Action Plan -- Step 6: Commitment and Accountability -- Step 7: Acknowledgment -- Step 8: Follow-Up -- The Coach's Checklist for Chapter 12 -- 13. Once More, with Feedback -- Elements of Effective Feedback -- Before You Deliver Feedback -- Delivering Bad News -- Feedback on Your Feedback -- The Coach's Checklist for Chapter 13 -- 14. Coaching and Rewards -- Tangible Rewards -- Symbolic Rewards -- Intangible Rewards -- Rules of Rewarding -- The Coach as a Cheerleader -- The Coach's Checklist for Chapter 14 -- 15. Principles of Good Coaching (and Good Living) -- The Principle of Getting Started -- The Illusion of Control -- The Principle of Decisions -- The Principle of Change -- The Principle of Time -- The Principle of Questions -- The Principle of Mistakes -- The Principle of Anger -- The Illusion of Objectivity -- The Principle of the Big Picture -- The Principle of Fear -- The Principle of Role Modeling -- The Principle of Life -- The Coach's Checklist for Chapter 15.
"Briefcase books."-- Covers
"Learn the different attributes of a good coach; Acquire the eight traits of an effective coach; Tap into the hidden motivation of your workforce."-- Cover
Includes bibliographical references and indexes.
Also issued in print and PDF version.
Description based on cover image and table of contents, viewed on Aug. 21, 2014.
Keywords: Employees -- Coaching of; Employees -- Training of; Employee motivation; Mentoring in business; Supervision of employees; Electronic books